2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28982
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Identity Fit on Engineering Doctoral Student Motivation and Performance

Abstract: Her research focus lies in engineering education across P-24. Her projects involve investigations of unplugged computer science lessons in K-12, identifying how machine learning can facilitate formative assessment, and understanding the motivation and identities of engineering students. Her education includes a minor in Mechanical Engineering, a B.S. in Secondary Education in Math, and a M.S. in Equity and Diversity from the University of Nevada, Reno.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…Identity-Based Motivation Items. Items for the identity-based motivation (IBM) survey were developed based on Oyserman's theory of Identity-Based Motivation (IBM) and the results from the authors' previous qualitative study [13]. Based upon Oyserman's theory, three central tenants of IBM were identified for inclusion in the survey: dynamic construction, action-readiness, and interpretation of difficulty.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identity-Based Motivation Items. Items for the identity-based motivation (IBM) survey were developed based on Oyserman's theory of Identity-Based Motivation (IBM) and the results from the authors' previous qualitative study [13]. Based upon Oyserman's theory, three central tenants of IBM were identified for inclusion in the survey: dynamic construction, action-readiness, and interpretation of difficulty.…”
Section: Methodsmentioning
confidence: 99%
“…As the first step in this process, three qualitative studies were conducted with an EDS sample [11]- [13]. This was done both to investigate whether EDS framed their experiences and identities similarly to previous undergraduate populations, and to begin exploring questions for the planned quantitative phase.…”
mentioning
confidence: 99%
“…Previous work found that a lack of advisor supervision was detrimental to graduate students' persistence in graduate programs [34], [35]. However, our previous work on EGSs [14] suggested that increasing EGSs' autonomy to conduct research tasks helped their identity development. Thus, finding the balance between too much and too little support is important [36].…”
Section: Discussionmentioning
confidence: 88%
“…Such research also showed that subtle environmental cues directly influenced which identities came to the students' minds and how students made sense of those identities within those environments. Within engineering graduate education, qualitative results indicated that a strong salient identity during task completion was important for increasing a student's motivation [14]. For this study, we focused on two IBM constructs: dynamic construction and perceived difficulty.…”
Section: Theoretical Framework: Identity-based Motivationmentioning
confidence: 99%
See 1 more Smart Citation